Australia's evolving food practices: a risky mix of continuity and change. Issue 14 (22nd September 2016) - Venn, Danielle; Banwell, Cathy; Dixon, Jane
Abstract: Objective: To investigate trends in five key aspects of Australian food practice which have been implicated in diet-related health risks, specifically energy intake. They are: the replacement of home-prepared foods by commercially prepared foods; consumer reliance on ultra-processed foods; de-structured dining; increased pace of eating; and a decline in commensal eating. Design: Data were from repeated cross-sections from the national Household Expenditure and Time Use Surveys. Trends in food practice aspects were examined using indicators of food expenditure across different food groups and time spent eating and cooking, including where, when and with whom eating activities took place. Setting: Australia, 1989–2010. Subjects: Nationally representative samples of Australian households. Results: The share of the total food budget spent on food away from home rose steadily from 22·8 % in 1989 to 26·5 % in 2010, while spending on ultra-processed foods increased. The basic patterning of meals and the pace of eating changed little, although people spent more time eating alone and at restaurants. Cooking time declined considerably, particularly for women. Conclusions: These changes have occurred over the same time that obesity and diet-related, non-communicable diseases have increased rapidly in Australia. Some aspects are implicated more than others: particularly the shift from domestic cooking to use of pre-prepared and ultra-processed foods, a reduction in time spent in food preparation and cooking, as well as an upsurge in time and money devoted to eating away from home. These are all likely to operate through the higher energy content of commercially prepared, compared with unprocessed or lightly processed, foods.